Gaya Kepemimpinan Transformasional Kepala Sekolah dan Kinerja Guru SMK Swasta di Jakarta Timur - Army Cahya Putra Rustamaji; Dedi Purwana; Corry Yohana (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2017)
This study aims to examine the effect of transformational leadership on teacher performance, job satisfaction and job attachment, the influence of work attachment to teacher performance, the influence of job satisfaction on teacher performance, direct influence between transformational leadership on teacher performance mediated by job satisfaction, and influence between transformational leadership of teacher performance mediated by work attachment. The result of the research shows that tranasformational leadership toward performance and job satisfaction have positive and significant influence. However, job satisfaction on teacher performance has no significant effect. Transformational leadership of performance mediated by job satisfaction shows a significant influence. Furthermore, transformational leadership towards work attachment has a positive and significant effect. Likewise on the variable attachment of work to performance. Furthermore, transformational leadership significantly affects employee performance with work attachment as a mediating variable. Keywords: Transformational Leadership, Job Satisfaction, Performance